Effect of particle proximity on changing of diffusion mechanism of 3Y-TZP nanoparticles at the initial stage of sintering. (February 2021) - Danilenko, Igor; Lakusta, Marharyta; Loladze, Larisa; Volkova, Galina; Glazunova, Valentina; Nosolev, Igor; Akhkozov, Leonid; Konstantinova, Tetyana
Abstract: In order to evaluate the effect of interparticle contact area on the sintering behavior of 3Y-TZP nanopowder, the shrinkage of powder samples, compacted at different pressures were measured under constant rates of heating. Compaction of zirconia NPs at different pressures allowed to increase the contact area between particles and determined the critical parameters when the volume diffusion mechanism is changing on the grain boundary diffusion. It was found that the volume diffusion mechanism is the dominant densification mechanism at the initial stage of sintering for 3Y-TZP nanopowders at a low relative density of green ceramics, when there are few contacting particles, and the grain boundary diffusion mechanism cannot be realized due to the large diffusion path. The domination of the grain boundary diffusion mechanism during initial stage of sintering of 3Y-TZP nanoparticles was detected in case the contact area between particles increased up to 56%. Highlights: The effect of isostatic pressure compaction on the sintering of 3Y-TZP NPs was studied. The contact area between particles effects on the diffusion mechanism during sintering. The critical value of the interparticle contact area when GBD realized is ca 56%. The VD mechanism can be realized in case of low contact area between particles.